The Effect of the Moscow Theatre Siege on Expectations of Well-Being in the Future - Vorsina, Margarita (Journal of interpersonal violence, 2021)
We employ the Russia Longitudinal Monitoring Survey–Higher School of Economics (RLMS-HSE), a survey of 6,000 individuals, and a difference-in-differences estimation strategy to examine the effect of the 2002 Moscow theatre siege on the level of self-reported expectations of life in the future of the Russian population. The longitudinal nature of the data allows us to explore both the short- and long-term effects of terrorism on this population as well as contribute to the limited number of quasi-experimental studies in this area. By focusing on expectations of life in the future, we broaden our understanding of the social consequences of terrorism. Controlling for a range of sociodemographic variables including self-assessed relative income, our findings suggest that the well-being effects of terrorism are complex and the net effect of a terrorism incident on well-being may not necessarily be negative. This can be explained, at least in part, by the theory of posttraumatic growth—a theory that refers to the positive psychological change experienced as a result of adversity, with terrorism incidents inadvertently promoting more meaningful interpersonal relationships, new views of the self and new views of the world. That is not to suggest that terrorism is a positive phenomenon—rather, that individuals have a lifelong plasticity rendering them capable of recovery from adversity. The primary objectives of terrorists, therefore, are unlikely to be fully achieved. It is hoped that our research allows for the development of more refined policies that aim to encourage posttraumatic growth while simultaneously attempting to minimize posttraumatic stress disorder. This may involve engaging with the psychological community to devise policies and programs that target those in the population who are most vulnerable and for these groups devise strategies to enhance their psychological resilience following a terrorist (or other traumatic) event.